Effect of COVID-19 on catastrophic medical spending and forgone care in Nigeria - Henry Chukwuemeka Edeh; Alexander Uchenna Nnamani; Jane Oluchukwu Ozor (Economies, 2025)
In this study, we provide the first estimates of the effect of COVID-19 (COVID-19 legal restrictions) on catastrophic medical expenditure and forgone medical care in Africa. Data for this study were drawn from the 2018/19 Nigeria General Household Survey (NGHS) panel and the 2020/21 Nigeria COVID-19 National Longitudinal Phone Survey panel (COVID-19 NLPS). The 2020/21 COVID-19 panel survey sample was drawn from the 2018/19 NGHS panel sample monitoring the same households. Hence, we leveraged a rich set of pre-COVID-19 and COVID-19 panel household surveys that can be merged to track the effect of the pandemic on welfare outcomes. We found that the COVID-19 legal restrictions decreased catastrophic medical expenditure (measured by out-of-pocket (OOP) expenditures exceeding 10% of total household expenditure). However, the COVID-19 legal restrictions increased the incidences of forgone medical care. The results showed a consistent positive effect on forgone medical care across waves one and two, corresponding to full and partial implementation of COVID-19 legal restrictions, respectively. However, the negative effect on catastrophic medical spending was only observed when the COVID-19 legal restrictions were fully in force, but the sign reversed when the restriction enforcement became partial. Moreover, our panel regression analyses revealed that having health insurance is associated with a reduced probability of incurring CHE and forgoing medical care relative to having no health insurance. We suggest that better policy design in terms of expanding the depth and coverage of health insurance will broaden access to quality healthcare services during and beyond the pandemic periods.
Keywords: I12; I13; I14; I18; 330; COVID-19; catastrophic medical expenditure; forgone medical care; legal restriction